2021
DOI: 10.3390/ijerph182211970
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis and Clinical Significance of In-Stent Restenosis in Patients with Diabetes

Abstract: Diabetes mellitus (DM) is a strong risk factor for the development of cardiovascular diseases such as coronary heart disease, cerebrovascular disease, and peripheral arterial disease (PAD). In the population of people living with DM, PAD is characterised by multi-level atherosclerotic lesions as well as greater involvement of the arteries below the knee. DM is also a factor that significantly increases the risk of lower limb amputation. Percutaneous balloon angioplasty with or without stent implantation is an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 176 publications
(165 reference statements)
1
48
0
Order By: Relevance
“…Therefore, anti-inflammatory medications may ameliorate diabetes, preventing its progression and vascular complications. More importantly, prospective studies have indicated that diabetic patients have a two- to four-fold risk of developing coronary artery disease and myocardial infarction [ 25 ], establishing that T2DM is an independent risk factor for cardiovascular disease (CVD) [ 25 , 26 , 27 ]. Indeed, there is evidence that the interaction of T2DM and related cardiovascular risk underpins the progressive nature of the vascular damage, leading to atherosclerosis [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, anti-inflammatory medications may ameliorate diabetes, preventing its progression and vascular complications. More importantly, prospective studies have indicated that diabetic patients have a two- to four-fold risk of developing coronary artery disease and myocardial infarction [ 25 ], establishing that T2DM is an independent risk factor for cardiovascular disease (CVD) [ 25 , 26 , 27 ]. Indeed, there is evidence that the interaction of T2DM and related cardiovascular risk underpins the progressive nature of the vascular damage, leading to atherosclerosis [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, biomarker monitoring can be used during the follow-up to evaluate the adequacy of therapy and the evolution of the disease. Jakubiak GK et al, in a review of the literature, about the current state of knowledge of mechanisms and the clinical significance of restenosis and in-stent restenosis (ISR), in patients with diabetes and PAD, reported an association between an elevated postoperative high-sensitivity C-Reactive Protein (hs-CRP) level, associated with an increased risk of ISR in one-year follow-up in patients who have undergone angioplasty [ 26 ]. In another study, the average hs-CRP level was shown to be significantly higher in patients in whom ISR had occurred [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Jakubiak et al also indicated in their literature review that the characteristics of frailty may well affect the clinical course of this condition, treatment efficacy, and complications of chronic lower limb ischaemia [ 35 ]. Moreover, the inflammatory process entailed in the pathogenesis of FS is also encountered in the pathogenesis of atherosclerotic cardiovascular disease and restenosis, following its endovascular treatment, as well as with regard to peripheral arteries [ 36 ].…”
Section: Frailty Syndromementioning
confidence: 99%